Serum C-Reactive Protein A Helpful Marker in Diagnosis of Acute Appendicitis - Wasif Baig, Haseeb Ahmad, Zaryab Shafiq, Adeel Khalid Choudhary, Muhammad Faisal Javaid, Khumair Asif (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: evaluate the diagnostic accuracy of serum C-reactive protein levels in acute appendicitis (AA) Methodology: Two hundred suspicious cases of AA presenting with pain in right iliac fossa in addition to nausea/vomiting, direct tenderness in right iliac fossa of either gender in adult population were included. Intravenous blood sample was drawn for CRP evaluation. Appendectomy was performed in all these cases, and histopathological examination was done to confirm presence/absence of AA. Both the reports were evaluated and AA was considered positive if CRP levels are >6 μg/dl. A 2x2 table was drawn to analyze diagnostic accuracy of CRP. Results: The mean age was 27.11+10.42 years, 80.5% (n=161) cases were diagnosed as acute appendicitis on histopathology. The diagnostic accuracy of serum C-Reactive Protein levels shows 81.63% for sensitivity, 73.58% for specificity, 89.55% had positive predictive value, 50.09% negative predictive value while 79.50% had accuracy rate. Conclusion: serum C-reactive protein levels is a useful marker for diagnosing acute appendicitis and may be used in rural areas where USG and CT scan facility is not available.